Dilute acid and ionic liquid based pretreatment of lignocellulosic biomass towards fermentable sugars - Dash, Madhusmita (My University, 2017)
The current study focuses on physico-chemical characterization and pretreatment of three commonly available lignocellulosic biomasses of North-East India such as Castor (Ricinus communis), Jatropha (Jatropha curcas), and Miscanthus (Miscanthus Sinensis) for second generation biofuels production. It was found that the cellulose content of three biomasses varied from 40% to 44%, hemicellulose content from 8% to 14% and lignin content varied from 21% to 30%. Chemical structure of lignocellulose is studied through FTIR. The crystallinity index of Castor and Jatropha was similar, i.e., 69%, whereas crystallinity index of Miscanthus was 72%. Due to the presence of higher carbon and cellulose content along with less moisture (10%–12%), ash (5%–10%), sulphur (0.1%– 0.8%), and extractives (12%–20%) makes them very good feedstock for the production of alcoholic fuels through biochemical route. Thermogravimetric analysis of these three lignocellulosic biomass under high purity nitrogen atmosphere were carried out over a temperature range of 25 oC–900 oC at three different heating rates of 10, 15, 20 oC min–1. The activation energy and pre-exponential factors were calculated by applying two modelfree methods and compared. The kinetic parameters obtained from Kissinger and Ozawa methods were in good agreement with the experimental results. The value of kinetic parameters explained the thermal stability of the biomass. The thermal analysis could not infer the composition and chemical structure of lignocellulosic biomass; hence FTIR spectroscopic analysis has been carried out.
Mohanty, Kaustubha
Veeranki, Venkata Dasu
Keywords: ENERGY SCIENCE AND ENGINEERING